Cardiovascular Disease and COVID-19: Insight From Cases With Heart Failure - Yi, Yang; Xu, Yanan; Jiang, Haibing; Wang, Jun (Frontiers in Cardiovascular Medicine, 2021)
Recent evidence indicates that a large proportion of deaths from coronavirus disease 2019 (COVID-19) can be attributed to cardiovascular disease, including acute myocardial infarction, arrhythmias and cardiac failure. Indeed, severe infection increases the risk of cardiac failure among patients with COVID-19. In most patients, cardiac failure arises from complex interactions between pre-existing conditions, cardiac injury, renin-angiotensin system activation, and the effects of systemic inflammation on the cardiovascular system. In this review, we summarize current knowledge regarding pathogen-driven cardiac failure occurring during treatment for COVID-19, the potential effects of commonly used cardiovascular and anti-infective drugs in these patients, and possible directions for establishing a theoretical basis for clinical treatment.